Relationship between Adolescents' Knowledge About Preventing Anemia During Menstruation - Safitri, Milda; Siagian, Lastini; Noviyanti, Asri; Sabrina, Dwi Gita (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Anemia is a medical condition where the number of erythrocytes and hemoglobin are abnormal. Hemoglobin levels in women and men are different. Anemia is a condition where hemoglobin, hematocrit and erythrocyte count decrease. (Kulsum, 2020). This research uses a descriptive analytical research design, namely the relationship between young women's knowledge about anemia and preventive behavior. The research design carried out was cross sectional, that is, data collection was carried out simultaneously while collecting the questionnaire. The population of this study was all 70 young women who had experienced menstruation. The results, the majority of respondents had good knowledge, 36 respondents (51.4%) and based on anemia prevention behavior, the majority of respondents had bad behavior, 38 respondents (54.3%), it can be explained that of the 70 female students, the majority had good knowledge, 22 respondents (31.5%). %) prevent anemia, while 24 respondents (34.2%) with poor knowledge do not prevent anemia during menstruation. Based on the table above, it can be seen that there is knowledge of young women about anemia with anemia prevention behavior during menstruation at the Kampung Baru Community Health Center, Tanjung Balai City in 2023 with a p value of 0.009. Conclusion: The relationship between young women's knowledge about anemia and behavior to prevent anemia during menstruation at the Kampung Baru Community Health Center, Tanjung Balai City in 2023 with a total of 70 respondents. There is a significant relationship with a p value of 0.009, where respondents who have good knowledge prevent anemia during menstruation. This research uses a descriptive analytical research design, namely the relationship between young women's knowledge about anemia and preventive behavior.. There is a significant relationship with a p value of 0.009, where respondents who have good knowledge prevent anemia during menstruation. KEYWORDS: anemia,knowledge, adolescence, menstruation, nutrition